Helium Irradiation and Implantation Effects on the Structure of Amorphous Silicon Oxycarbide - Qing Su (Nature Portfolio, 2017)
Abstract Despite recent interest in amorphous ceramics for a variety of nuclear applications, many details of their structure before and after irradiation/implantation remain unknown. Here we investigated the short-range order of amorphous silicon oxycarbide (SiOC) alloys by using the atomic pair-distribution function (PDF) obtained from electron diffraction. The PDF results show that the structure of SiOC alloys are nearly unchanged after both irradiation up to 30 dpa and He implantation up to 113 at%. TEM characterization shows no sign of crystallization, He bubble or void formation, or segregation in all irradiated samples. Irradiation results in a decreased number of Si-O bonds and an increased number of Si-C and C-O bonds. This study sheds light on the design of radiation-tolerant materials that do not experience helium swelling for advanced nuclear reactor applications.